Kinematics of the head and associated vertebral artery length changes during high-velocity, low-amplitude cervical spine manipulation - Lindsay M. Gorrell; Gregor Kuntze; Janet L. Ronsky; Ryan Carter; Bruce Symons; John J. Triano; Walter Herzog (Chiropractic & Manual Therapies, 2022)
Abstract Background Cervical spine manipulation (CSM) is a frequently used treatment for neck pain. Despite its demonstrated efficacy, concerns regarding the potential of stretch damage to vertebral arteries (VA) during CSM remain. The purpose of this study was to quantify the angular displacements of the head relative to the sternum and the associated VA length changes during the thrust phase of CSM. Methods Rotation and lateral flexion CSM procedures were delivered bilaterally from C1 to C7 to three male cadaveric donors (Jan 2016–Dec 2019). For each CSM the force–time profile was recorded using a thin, flexible pressure pad (100–200 Hz), to determine the timing of the thrust. Three dimensional displacements of the head relative to the sternum were recorded using an eight-camera motion analysis system (120–240 Hz) and angular displacements of the head relative to the sternum were computed in Matlab. Positive kinematic values indicate flexion, left lateral flexion, and left rotation. Ipsilateral refers to the same side as the clinician's contact and contralateral, the opposite. Length changes of the VA were recorded using eight piezoelectric ultrasound crystals (260–557 Hz), inserted along the entire vessel. VA length changes were calculated as D = (L1 − L0)/L0, where L0 = length of the whole VA (sum of segmental lengths) or the V3 segment at CSM thrust onset; L1 = whole VA or V3 length at peak force during the CSM thrust. Results Irrespective of the type of CSM, the side or level of CSM application, angular displacements of the head and associated VA length changes during the thrust phase of CSM were small. VA length changes during the thrust phase were largest with ipsilateral rotation CSM (producing contralateral head rotation): [mean ± SD (range)] whole artery [1.3 ± 1.0 (− 0.4 to 3.3%)]; and V3 segment [2.6 ± 3.6 (− 0.4 to 11.6%)]. Conclusions Mean head angular displacements and VA length changes were small during CSM thrusts. Of the four different CSM measured, mean VA length changes were largest during rotation procedures. This suggests that if clinicians wish to limit VA length changes during the thrust phase of CSM, consideration should be given to the type of CSM used.